2021
DOI: 10.1186/s13020-021-00458-7
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone I exerts cardiovascular protective effects in vivo and in vitro through inhibiting necroptosis via Akt/Nrf2 signaling pathway

Abstract: Background Tanshinone I (TI) is a primary component of Salvia miltiorrhiza Bunge (Danshen), which confers a favorable role in a variety of pharmacological activities including cardiovascular protection. However, the exact mechanism of the cardiovascular protection activity of TI remains to be illustrated. In this study, the cardiovascular protective effect and its mechanism of TI were investigated. Methods In this study, tert-butyl hydroperoxide (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Unsupervised learning algorithm has excellent feature learning ability, which is conducive to data classification [ 10 ]. Some studies pointed out that, in the process of unsupervised initialization, the introduction of greedy layer-by-layer unsupervised training method can improve the generalization performance of big data [ 11 ]. However, unsupervised deep learning is limited by computer hardware in the process of big data training, resulting in slow convergence [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unsupervised learning algorithm has excellent feature learning ability, which is conducive to data classification [ 10 ]. Some studies pointed out that, in the process of unsupervised initialization, the introduction of greedy layer-by-layer unsupervised training method can improve the generalization performance of big data [ 11 ]. However, unsupervised deep learning is limited by computer hardware in the process of big data training, resulting in slow convergence [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidences showed that the accumulation of ROS leads to increased cell mobility, remodeled the cytoskeleton, diminished cell–cell conjunctions and increased the EMT markers through NF-κB, HIF-1, p38 MAPK and PI3K/Akt pathways [ 40 – 42 ]. And the antioxidant agents such as NAC and MPG could attenuate EMT progression through decreasing the production of ROS [ 43 , 44 ]. Therefore, therapeutic targets on ROS could prevent the EMT induced cancer metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple signaling pathways are regulated by Tan-I, among which nuclear factor erythroid 2 related factor 2 (Nrf2) signaling was identified as an important target of Tan-I [ 25 27 ]. Nrf2 inhibits inflammation, oxidative stress and protects mitochondria function in chronic kidney diseases [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 inhibits inflammation, oxidative stress and protects mitochondria function in chronic kidney diseases [ 28 ]. Tan-I can directly activate Nrf2 as its potential agonist or indirectly activate Nrf2 through the Akt signaling pathway [ 25 27 ]. Thus, whether Tan-I inhibits renal interstitial fibrosis through Nrf2 warrants further study.…”
Section: Discussionmentioning
confidence: 99%